Mycobacteriosis in slaughter pigs from South Africa from 1991 to 2002: Mycobacterium spp. diversity and Mycobacterium avium complex genotypes - Gcebe, Nomakorinte; Pierneef, Rian Ewald; Michel, Anita Luise; Hlokwe, Motlatso Tiny (Frontiers in Microbiology, 2023)
Mycobacterium avium complex (MAC) bacteria are the most prominent etiological agents of lymphadenitis in pigs. Mycobacterium avium subspecies hominissuis (MAH) is a member of MAC and has been reported in many parts of the world to be the most prevalent nontuberculous mycobacteria (NTM) to cause mycobacteriosis in humans, mainly in children.Thus, the economic and zoonotic impact of MAC species are increasingly being recognised.In South Africa, little is known about the distribution of NTM and the molecular epidemiology of Mycobacterium avium in pigs. In this study, lymph nodes including mandibular, mesenteric , submandibular and retropharyngeal ,with tuberculosis like lesions were collected during routine meat inspection of slaughter pigs with no disease symptoms (n=132), between 1991 and 2002. These pigs were slaughtered at 44 abattoirs distributed across seven of the nine South African provinces. Mycobacterial culture, polymerase chain reaction (PCR), and sequencing of the Mycobacterium specific 577 bp 16S rRNA gene fragment were performed for species and subspecies identification. The majority of the isolates (each per sample); 114 (86. 4%) were identified as MAH, 8 (6%) as MAA/ Mycobacterium avium subsp sylvaticum, 4 (3%) were Mycobacterium tuberculosis, 2 (1.5%) as Mycobacterium intracellulare, and 1 (0.75%) as Mycobacterium bovis. The other isolates were identified as Mycobacterium lentiflavum (0.75%), Mycobacterium novocastrense (0.75%), and a Micrococcus spp (0.75%). Using an eight-marker MLVA typing tool, we deciphered at least nine MIRU VNTR INMV types of MAH and MAA.. Identification of known zoonotic mycobacteria, including MAH, MAA, M. intracellulare, M. bovis and M. tuberculosis, from slaughter pigs has a potential public health impact and also strengthens recognition of the potential economic impact of MAC. This study has also for the first time in South Africa, revealed MAC MIRU VNTR INMV genotypes which will aid in the future epidemiological investigation of MAC in South Africa.